Everyday-Carry Equipment Mapping: A Portable and Low-Cost Method for 3D Digital Documentation of Architectural Heritage by Integrated iPhone and Microdrone - Nan Zhang; Xijian Lan (Buildings)
Mapping constitutes a critical component of architectural heritage research, providing the groundwork for both conservation and utilization efforts. Three-dimensional (3D) digital documentation represents a prominent form of mapping in the contemporary era, and its value is widely recognized. However, cost and portability constraints often limit its widespread use in routine research and conservation initiatives. This study proposes a cost-effective and portable approach to 3D digital documentation, employing everyday-carry (EDC) equipment, the iPhone 15 Pro and DJI Mini 4 Pro, for data acquisition in architectural heritage. The workflow was subsequently optimized, and the datasets from the iPhone-LiDAR and microdrone were seamlessly integrated, resulting in an integrated 3D digital model of both the indoor and outdoor spaces of the architectural heritage site. The model demonstrated an overall relative error of 4.93%, achieving centimeter-level accuracy, precise spatial alignment between indoor and outdoor sections, clear and smooth texture mapping, high visibility, and suitability for digital display applications. This optimized workflow leverages the strengths of both EDC equipment types while addressing the limitations identified in prior studies.